Effect of dispersion particles and precipitates on the corrosion properties of ODS-Cu, Cu-Cr-Zr and Cu-Cr alloys in Na2SO4 solutions. (June 2022) - Hatakeyama, Masahiko; Okada, Kai; Sunada, Satoshi; Sato, Koichi
Highlights: Corrosion resistance of Cu alloys in a 0.1 M Na2 SO4 solution was evaluated. In ODS-Cu, oxide particles degraded protective performance of the passivation film. Precipitation hardened Cu alloys showed good corrosion resistance. Cu-Cr-Zr alloy showed corrosion due to the coarse columnar Cr precipitates. Abstract: Precipitation-hardened Cu-Cr-Zr alloy is proposed as a heat sink material for various components of the ITER (blanket first wall, divertor, electrical straps and others) owing to its high strength, high conductivity and superior resistance against neutron irradiation. ODS-Cu (Oxide Dispersion Strengthened Copper) is also selected as a candidate material. Corrosion properties of alumina-dispersed copper alloys (GlidCop® CuAl15, CuAl25), aevaluated by electrochemical methods in 0.1 M and 0.01 M sodium sulfate (Na2 SO4 ) solutions. In open circuit potential (OCP) measurement in 0.1 M Na2 SO4 solution, the potential of all alloys decreased immediately after immersion and then gradually decreased. CuAl15 showed good corrosion resistance in the OCP measurement with little potential drop. In the polarization curve measurements, a difference was observed for each material in the cathode region. The corrosion current densities tended to be higher for CuAl25 and Cu-Cr-Zr, and the corrosion potential was also low in both solutions. In these alloys, the surface observation after the polarization curve measurements showed variations in the thickness of the Cu2 O passivation film, and there were large areas where the film was thought to be thin. In Cu-Cr-Zr, coarse columnar Cr precipitates and segregation of Zr at the precipitate/matrix interface are thought to deteriorate corrosion resistance. In the case of CuAl25, it is suggested that dissolution of the passivation film is enhanced due to large volume fraction of alumina particles.